Patients’ Perspectives on Stigma of Mental Illness (an Egyptian Study in a Private Hospital) - Sidhom, Emad; Abdelfattah, Ahmed; Carter, Julie M.; El-Dosoky, Ahmed; El-Islam, Mohamed Fakhr (Frontiers in Psychiatry, 2014)
The present study is concerned with the stigma of mental illness. It examines the subjective element of the experience of stigma among a sample of in-patients with different mental disorders. The sample was taken from consecutive admissions of in-patients meeting ICD-10 criteria for mental disorders who had capacity to decide on participation in the study and were willing to respond to the structured interview. The study was undertaken in an Egyptian private psychiatric hospital. The structured clinical interview included aspects of the emotional, behavioral and cognitive effects of having a psychiatric diagnosis on in-patients with various diagnostic labels in an Egyptian psychiatric hospital. It also studied whether this effect changes with specific disorders, total duration of illness or sociodemographic variables as gender, age or educational level. The study illustrated the core items of stigmatization attached to the diagnosis of mental illness (Sidhom et al, 2012), which more than half of the participants responded affirmatively. The study aimed to explore the most prevailing aspects of stigma or social disadvantage; hoping that this may offer a preliminary guide for clinicians to address these issues in their practice.